The Effect of Samisake Policy Implementation and Development on the Poverty of Jambi City People - Muhammad Sahlani (International Journal of Social Service and Research, 2023)
The SAMISAKE (One Billion One District) program is the belle of the 2010-2015 elected governor program. Implementation of the One Billion One District Program (SAMISAKE) and the Acceleration of Development is basically a program aimed at the poor through house renovations, free house certificates, scholarships, regional health insurance and UMKM facilities. This research is a survey research using explanatory research. The sampling technique in this study was proportionate stratified random sampling with a sample of 100 respondents. The instrument of data collection in this study was a questionnaire based on a Likert scale. Statistical analysis used was regression analysis with SPSS version 25. Data collection methods used literature study techniques, questionnaires, documentation studies and observations. The results of the study prove that: (i) Implementation of the Samisake Policy has a positive and significant impact on the poverty of the people of Jambi City, which is 86.1%. (ii) Development has a positive and significant impact on the poverty of the people of Jambi City, which is 90%. (iii) The implementation of the Samisake Policy and development together has a positive and significant impact on the poverty of the people of Jambi City, which is 90%. From this research, it can be seen and proven that development of 0.900 or 90% has an effect on the poverty of the people of Jambi City and then the implementation of the Samisake Policy is 0.861 or 86.1% of the poverty of the people of Jambi City who jointly implement the Samisake Policy and Development on the poverty of the people of the city. Jambi is 90%.